Effect of increased vacuum and aspiration rates on phacoemulsification efficiency. Issue 4 (April 2015) - Gupta, Isha; Cahoon, Judd M.; Gardiner, Gareth; Garff, Kevin; Henriksen, Bradley S.; Pettey, Jeff H.; Barlow, William R.; Olson, Randall J.
Abstract : Purpose : To evaluate the effect of vacuum and aspiration rates on phacoemulsification efficiency. Setting : John A. Moran Eye Center Laboratories, University of Utah, Salt Lake City, Utah, USA. Design : Experimental study. Methods : Formalin‐soaked porcine lenses were divided into 2.0 mm cubes, and 0.9 mm 30‐degree beveled 20‐degree bent tips were used with micropulse ultrasound (US) (6 milliseconds on and 6 milliseconds off) and a peristaltic flow system. Vacuum levels were tested at 200, 300, 400, and 500 mm Hg, and aspiration rates were tested at 20, 35, and 50 mL/min. Efficiency (time to lens removal) and chatter (number of lens fragment repulsions from the tip) were determined. Results : Increasing vacuum increased efficiency only when going from 200 mm Hg to higher vacuum levels. Increasing aspiration increased efficiency at all points measured (25 mL/min versus 35 mL/min, P < .0001; 35 mL/min versus 50 mL/min, P = .012; 25 mL/min versus 50 mL/min, P < .0001). Chatter was highest at 200 mm Hg and decreased when vacuum was increased from 200 mm Hg to 300 mm Hg and up. Chatter decreased with increasing flow. Conclusions : Vacuum improved efficiency only up to 300 mm Hg and was more dependent on increasing flow. Similarly, chatter correlated with 200 mm Hg vacuum only and was more correlated with flow. Limitations of this study include use of only 1 US power modulation and hard nuclear material. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.